Exposure dependent increase in DNA single strand breaks in leucocytes from workers exposed to low concentrations of styrene. Issue 6 (June 1993) - Walles, S A; Edling, C; Anundi, H; Johanson, G
Abstract : Single strand breaks in DNA were monitored in leucocytes from 17 men occupationally exposed to styrene. Personal air monitoring was carried out during one workday with two diffusion samplers and a portable photoionisation detector placed in the breathing zone. Exposure to styrene was also monitored by analysing styrene in blood and urine and mandelic acid in urine. Single strand breaks were measured in leucocytes by the alkaline elution technique. The biological samples were collected before a shift, at the end of a shift, and the next morning, before the next shift. An exposure dependent increase in single strand breaks was seen at the end of a shift but not before a shift or the next morning. Linear regression analysis indicated that the amount of DNA damage was roughly doubled after eight hours of exposure to 18 ppm styrene or at a urine concentration of 240 mg mandelic acid/g creatinine compared with the damage in non-exposed men. This study indicates that monitoring of single strand breaks with the alkaline elution technique may be a sensitive marker of genotoxic effects. To our knowledge, this is the first time that such a marker has been shown to correlate with exposure to less than 20 ppm styrene.